2009
DOI: 10.1073/pnas.0903311106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrinsic organic carbon on the optical properties of fresh diesel soot

Abstract: This study focuses on the retrieval of the normalized mass absorption cross section (MAC) of soot using theoretical calculations that incorporate new measurements of the optical properties of organic carbon (OC) intrinsic to fresh diesel soot. Intrinsic OC was extracted by water and an organic solvent, and the complex refractive index of the extracted OC was derived at 532 and 355-nm wavelengths using cavity ring-down aerosol spectrometry. The extracted OC was found to absorb weakly in the visible wavelengths … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
140
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 49 publications
7
140
0
2
Order By: Relevance
“…If we assume that coating by non-or weakly-absorbing aerosol results in a ∼35 % enhancement then our reduced MAE value of 7.0 +/ 0.6 m 2 g −1 at 530 nm is in good agreement with the value of 7.5±0.3 m 2 g −1 (@550 nm) reported for BC in the review by Bond et al (2006) and 7.1 m 2 g −1 recently reported for diesel soot (Adler et al, 2010). If absorption by uncoated BC is being over estimated by 80 % then a reduced value of ∼5.3 m 2 g −1 is comparable to Fuller et al (1999) who reported an MAE value of 5.4 m 2 g −1 for amorphous graphitic spheres from diesel soot.…”
Section: Mass Absorption Efficiency Of Light Absorbing Carbonsupporting
confidence: 80%
“…If we assume that coating by non-or weakly-absorbing aerosol results in a ∼35 % enhancement then our reduced MAE value of 7.0 +/ 0.6 m 2 g −1 at 530 nm is in good agreement with the value of 7.5±0.3 m 2 g −1 (@550 nm) reported for BC in the review by Bond et al (2006) and 7.1 m 2 g −1 recently reported for diesel soot (Adler et al, 2010). If absorption by uncoated BC is being over estimated by 80 % then a reduced value of ∼5.3 m 2 g −1 is comparable to Fuller et al (1999) who reported an MAE value of 5.4 m 2 g −1 for amorphous graphitic spheres from diesel soot.…”
Section: Mass Absorption Efficiency Of Light Absorbing Carbonsupporting
confidence: 80%
“…From the climate change point of view, reductions in EC aerosol emissions could reduce the positive radiative forcing effect associated with diesel PM emissions (Gaffney and Marley 2009), and since OC aerosol species tend to have a negative radiative forcing effect (Adler et al 2009) their warming effect might as well be reduced. In regards to OC aerosol emissions, there was little variation for B25, B50, and B75 blends, however, using pure biodiesel fuel (B100) resulted in increases in overall OC aerosol emission rates, mostly associated with unburned fatty acid methyl esters.…”
Section: Discussionmentioning
confidence: 99%
“…Both laser powers give a collection efficiency of over 80% for rBC mass >0.2fg. Considering that the size of primary spherules of soot are 30-50nm 28 , equivalent to D ve in the range 0.02-0.1fg, this SP2 detection efficiency is sufficient to measure the small rBC.…”
Section: Figure Captionsmentioning
confidence: 99%